(untitled) - Boss, Judith A. (Boston, MA., 2005)
System requirements for accompanying CD-ROM: Windows: IBM PC, Pentinum processor, microsoft windows, 98 SE/2000/ME/XP/NT 4.0 SF, 800x600 resolution, internet browser; MacIntosh: power PC or higher processor, MAC OS 9.2 or OS X classic 9.
Keywords: Ethical problems,Applied ethics